Recurrent mutation in the human phenylalanine hydroxylase gene. - Okano, Y (1990)
We report the identification of a missense mutation of Glu280 to Lys280 in the phenylalanine hydroxylase (PAH) gene of a phenylketonuria (PKU) patient in Denmark. The mutation is associated with haplotype 1 of the PAH gene in this population. This mutation has previously been found in North Africa, where it is in linkage disequilibrium with haplotype 38. While it is conceivable that this mutation could have been transferred from one haplotype background to another by a double crossover or gene conversion event, the fact that the mutation is exclusively associated with the two different haplotypes in the two distinct populations supports the hypothesis that these two PKU alleles are the result of recurrent mutations in the human PAH gene. Furthermore, since the site of mutation involves a CpG dinucleotide, they may represent hot spots for mutation in the human PAH locus.